Implementation of the Regional Government Information System (SIPD) at the Takalar Regency Regional Financial and Revenue Management Agency - Wahyuni; Linda Arisanty Razak; Nurul Anriani (IECON, 2024)
The aim of this research is to find out how the Regional Government Information System (SIPD) is implemented in Takalar. This research was carried out using the case study analysis method, where this approach focuses on in-depth study of certain phenomena with the aim of understanding the phenomenon in detail. Data collected through interviews with Regional Financial and Asset Agency agencies in the Budget section, observations and documentation in the form of financial reports. Informant: Mr. Syamsul Kamar as the Budget Subdivision of the Regional Financial and Asset Agency (BKAD). The data analysis methods used are the Miles and Huberman approach, including: Data collection, Anticipatory, Data Reduction, Data Display, Verification/drawing conclusions. The results of the research show that the use of the Regional Government Information System (SIPD) application has played a very important role in decision making at the Takalar Regency Regional Financial and Asset Agency (BKAD), where this application is able to manage regional financial data (regional budget planning, implementation and administration of regional finances, regional financial accounting and reporting, accountability for regional financial implementation, accountability for regional property and other regional financial information) through relevant stakeholders more effectively and efficiently by paying attention to the principles of accountability and transparency, despite the problems experienced in the government information system process, which often activities and input processes in the field are hampered due to poor networks and not being able to back up data. However, this does not reduce the function of the government information system in decision making. And the quality of information from the SIPD application is quite complete, because this application provides accurate information to stakeholders, thus enabling more appropriate decision making.